Charcoal-related forest degradation dynamics in dry African woodlands: Evidence from Mozambique. (June 2019) - Silva, Julie A.; Sedano, Fernando; Flanagan, Steve; Ombe, Zacarias A.; Machoco, Rene; Meque, Cardoso H.; Sitoe, Almeida; Ribeiro, Natasha; Anderson, Kelly; Baule, Susana; Hurtt, George
Highlights: Dry woodlands are progressively degraded by three distinct, sequential charcoal production waves. Even extremely selective charcoal production systems cause considerable modification to forest structure. The environmental consequences of an expanding producer population are more serious than charcoal poverty traps.